Адаптивний алгоритм керування рухом на регульованому Т-подібному перехресті - Могила, Ігор; Дяк, Марія; Шварик, Ігор (Видавництво Львівської політехніки, 2013)
Adaptive algorithms for traffic control at signalized intersections are analyzed and it is shown that there is no universal algorithm which is simple in software and practical implementation. The algorithm for control at T-shaped signalized intersection is proposed. The algorithm extends green light if volume is high or switches on the next stage if it is the long queue at the conflict direction. It is determined based on simulating results of signalized intersection functioning in VISSIM software that proposed algorithm is more efficient in comparison with fixed-time control irrespective of distance between detectors at the intersection approach.
Keywords: адаптивний алгоритм керування; регульоване перехрестя; імітаційне моделювання; VISSIM